The effect of Service Quality Dimension toward Customer Satisfaction at Pesona Resort in Gili Trawangan Lombok (Study on Pesona Resort in Gili Trawangan Lombok) - Riadistira, Fareza Novandro (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of Service Quality Dimension consisting of five dimensions, namely Tangible (X1), Reliability (X2), Responsiveness (X3), Assurance (X4), and Empathy (X5) towards Customer Satisfaction (Y) at Pesona Resort in Gili Trawangan Lombok. To find out how the influence of these independent variables (quality of service) on the dependent variable (customer satisfaction), used multiple linear regression analysis is used where F test and t test are used test hypotheses. This research is included in types of explanatory research studies. In accordance to the objectives of this study, it describes the relationship with the influence of several variables that have been defined. This study used a sample of 161 customer of Pesona Resort in Gili Trawangan Lombok, and the sampling technique used is purposive sampling. To obtain good results of the regression, the regression testing prior to first test the research instrument in the form of validity test, reliability test, and also classical assumption test. The results of regression indicate that service quality simultaneously significant influence to the satisfaction of service users, with a value of 76,230. Partially, quality of service significantly influence satisfaction with the service user through tcount each of independent variable 2,249 for tangible (X1),Â  reliability of 2,755 (X2) , responsiveness (X3) of 4,363,Â  assurance (X4) of 3.932, and empathy (X5) of 2,206. Adjusted R2 value of 0,702 which means 70,2% customer satisfaction is influenced by the independent variable examined, while the remaining 29,8% are influence by another variable outside the research. The fifth dimension of service quality has a positive or direct relationship with customer satisfaction. Based from this study, empirical evidence gained can be used as the basis towards idea of more in-depth study about the effect of service quality dimensions to the service user satisfaction. Keywords: SERVQUAL, Customer Satisfaction, Pesona Resort, Lombok.